Development of High-Performance UV Detector Using Nanocrystalline Diamond Thin Film - C. R. Lin; D. H. Wei; M. K. BenDao; W. E. Chen; T. Y. Liu (International Journal of Photoenergy)
Nanocrystalline diamond (NCD) films are promising materials for wide-spread applications due to their outstanding characteristics of chemical, physical, and highly smooth surface. Our present work aimed at the fabrication of high performance diamond-based UV detector. NCD films were prepared by microwave plasma enhanced chemical vapor deposition process, and then Au interdigital electrodes were deposited onto the surface of the as-grown NCD film by sputtering technique. Annealing procedures were conducted at various temperatures to obtain Ohmic contact of NCD/Au structure. The surface morphology, microstructure, and wettablity of the NCD films were analyzed by scanning electron microscopy, atomic forced microscopy, Raman spectroscopy, X-ray photoelectron spectroscopy, transmission electron microscopy, and water contact angle measurement, respectively. The electrical property and photoconductivity of the fabricated devices were tested for UV detection application. It was found that the NCD films possessed high sp3 fraction of 68.6%, low surface roughness of 9.6 nm, and good hydrophobicity, as deposited under working pressure of 40 Torr. Also, the NCD/Au structure annealed at 500°C exhibited a good Ohmic contact characteristic, high detection efficiency, and fast response to UV irradiation in air ambient. The proposed study indeed demonstrates prospective applications of NCD films in UV detector, photocatalyst, solar cell, and so on.